What type of inhibition underpins performance on Luria's Fist-Edge-Palm task?. Issue 6 (2nd July 2020) - Varkovetski, Michael; Pihkanen, Kaisla; Shanker, Shanti; Parris, Benjamin A.; Gurr, Birgit
ABSTRACT: Objective: The Fist-Edge-Palm task is a motor sequencing task believed to be sensitive to frontal lobe impairment. The present study aimed to investigate the inhibitory processes underlying successful execution of this task. Method: Seventy-two healthy participants were asked to perform the Fist-Edge-Palm task paced at 120 bpms, 60 bpms and self-paced. They also completed assessments sensitive to recently dissociated forms of inhibition (the Hayling Sentence Completion Test and the Stroop Color-Word Test) that have recently been shown to be differentially lateralized (the right and left Prefrontal Cortex, respectively), and Cattell's Culture Fair Intelligence test. Results: Analysis revealed that performance on the Hayling Sentence Completion Test predicted the amount of crude errors and the overall score on the Fist-Edge-Palm task, and that pacing condition had no effect on this outcome. Neither the Stroop Color-Word Test nor Cattell's Culture Fair Intelligence Test predicted performance on the Fist-Edge-Palm task. Conclusions: Consistent with some previous neuroimaging findings, the present findings suggest that Fist-Edge-Palm task performance relies on right lateralized inhibitory processes.